The compliance of land-use planning with strategic spatial planning – insights from Zurich, Switzerland. Issue 7 (3rd July 2021) - Schmid, Franziska B.; Kienast, Felix; Hersperger, Anna M.
ABSTRACT: Although many planning systems are based on a combination of traditional land-use planning and strategic spatial planning, the interplay between the two approaches remains insufficiently investigated. Focusing on the Canton of Zurich, we applied a qualitative content analysis to extract strategic planning intentions from the Cantonal Structure Plan (1995). We quantitatively analysed the compliance of changes in municipal land-use plans between 1996 and 2016 concerning the extracted planning intentions. The overall low rate of changes was accompanied by few active contradictions of land-use planning. Minor deviations from the strategic plan were seen in the spatial allocation of new building zones. Considering the socio-economic dynamics of the region, surprisingly few changes were detected regarding the permitted building density for residential and mixed-use areas. This leads us to the conclusion that the Cantonal Structure Plan (1995) was very successful in quantitatively limiting the expansion of building zones. However, it showed a limited active steering capacity regarding their allocation and the regulation of building density. Our analysis showed that margins of discretion play a key role in multi-level planning systems, balancing flexibility for locally adapted solutions against statutory boundaries to prevent their misuse, as such they need to be considered in planning evaluation.